Introducing the bipolar solvent media using the aqueous mixtures of amino acid anion-based ionic liquids - Beniwal, Vijay; Kumar, Anil (Journal of Physical Chemistry B, 2017)
To carry out a chemical reaction between the reactants with largely different polarities, it becomes important to have a reaction medium that possesses both the polar and nonpolar solvation environments. In an attempt to explore the reaction media with such unique polarity properties, the present study provides a thorough understanding of the bipolar solvent media using the aqueous mixtures of amino acid anion-based ionic liquids. The highly polar behavior of the binary mixtures used in the study has been ascribed to the pure ionic liquid state. However, the less polar solvation shells have been attributed to the presence of a neutral form of the anions. Addition of water in the amino acid anion-based ionic liquids causes the protonation of a certain fraction of the anions of the ionic liquids, resulting into the formation of a less polar nonionic protonated form along with the highly polar natural anionic form. This results into the formation of two solvation spheres with different polarities, which can be seen very clearly from the presence of two absorption bands (lower wavelength absorption band and higher wavelength absorption band) in the UV-vis absorption spectrum of Reichardt's E-T(30) dye and two emission bands (lower wavelength emission band and higher wavelength emission band) in the fluorescence emission spectrum of C481 dye. The values of the E-T(N) polarity parameter corresponding to the two solvation shells having different polarities have been calculated from the deconvoluted absorption spectra of the Reichardt's E-T(30) and were analyzed in three amino acid anion-based ionic liquids. Generation of the neutral form of anions in the aqueous mixtures formed via a protonation transfer reaction has been confirmed by the H-1 NMR spectroscopy and UV-vis absorption spectrum of 18DHAQ dye. The study also establishes that the Reichardt's E-T(30) dye can be used as a valid polarity probe to study the solvatochromic behavior of the binary mixtures of amino acid-based ionic liquids.